Development of Garuda Mas Tourism Object Based on Educational Tourism in Agam Regency, West Sumatera - Arsih, Fitri; Fajrina, Suci; Syafrini, Delmira; Yuanda, Tazkiyah; Salsabila, Ghina (Fakultas MIPA Universitas Negeri Padang, 2024)
Community training in developing educational tourism is a strategic effort to combine aspects of education and tourism to create an interactive and enjoyable learning experience. Garuda Mas is one of the tourist attractions in Nagari Manggopoh, Lubuk Basung District, Agam Regency, West Sumatra Province. This tourist attraction has the potential to be developed into educational tourism. However, the development of this educational tourism object is faced with various obstacles that need to be overcome, such as the unavailability of human resources. The development of tourist attractions that provide interesting learning experiences requires a fairly large investment, including the provision of quality educational content and training for staff who will become education facilitators. Another obstacle is the lack of understanding or support from the local community regarding the importance of educational tourism. The purpose of this community partnership program is to provide training to tourism awareness groups at the Garuda Mas Tourist Attraction in an effort to develop it into an educational tourism-based tourist attraction. The implementation method for developing the Garuda Mas tourist attraction based on educational tourism used is Oriented-Project Planning (OPP). Based on the results, it can be seen that the training on the development of Garuda Mas Tourism Objects based on educational tourism in Agam Regency, West Sumatra Province was able to increase participants' knowledge about the concept of educational tourism, development and management of educational tourism.